Estudo experimental e numérico da dinâmica de corpos moedores em moinhos de bola - Machado, Marcela Vieira Caixeta (2016)
Ball mills are used in several industrials sectors, such as cement, food and mining industries. Inside a ball mill, the comminution is performed by the grinding media movement and their interaction with the material to be broken. In this work, the grinding media dynamics in a ball mill with lifters was studied experimentally by the analysis the transitional phenomena between cascading, cataracting and centrifuging. In order to assess the end-walls effect in the behavior ball charge, both transitions were investigated for one, two or three layers of balls in the axial direction. The end-wall effect did not significantly influence the transitions between regimes. The centrifuging critical rotation speeds noted experimentally were compared to the centrifuging speeds given by literature equations which take into account some systems variables. These equations could not correctly predict the occurrence of centrifuging in a ball mill with lifters. Therefore, a centrifuging equation was adjusted for the steel-chrome balls used in this work. Coupled with experimental work, the grinding media dynamics was studied by simulations in computational fluid dynamics (CFD), using the commercial software FLUENT® and the Eulerian approach. The influence of boundary conditions in the walls was investigated by analysis the different values of specularity coefficient, considering the difficultly of measuring this parameter. It was found the influence of the specularity coefficient on the movement of grinding media simulation in ball mill. The values of this parameter that had greater physical consistency with the experimental observations are between 0,40-0,20. This observation confirms the required careful in the assignment of the boundary condition in the wall, especially the equipment is simulated in small scales and even though the end-wall effect was not observed in experimental study. Moreover, the grinding media movement was assessed for values of the ball restitution coefficient and it was not observed considerable differences.